The distribution of the carnivorous plant nepenthes (Nepenthaceae) in Marai Parai, Kota Belud, Sabah, Malaysia - Nur Farahim Mohd Zubir; Emmeldah Joseph; Nur Syamimi Makbul; Elia Godoong (Sabah Parks Nature Journal, 2024)
Nepenthes (Nepenthaceae), a carnivorous plant, is notable for its character and carnivory constancy. This genus provides an excellent structure for studying the taxonomy and evolution of Nepenthes in relation to their functions and habitats. However, because of the complexity of Nepenthes evolution and taxonomy based on morphological traits, it is challenging to resolve these issues based on phylogenetic relationships. There are approximately 20 Nepenthes species in Sabah, seven of which are endemic and can be found in protected areas, such as Kinabalu Park. In this study, we examined Nepenthes species and their distribution patterns in Marai Parai, Kota Belud, Sabah. Elevation levels, humidity, and temperature were recorded to determine and investigate the relationship between the distribution and environmental factors of the Nepenthes species. Nepenthes species in Marai Parai were identified morphologically together with their distribution patterns, and a correlation analysis between elevation, humidity, and temperature was performed. There was no significant relationship between humidity and temperature with elevation; however, there was a significant relationship between humidity and temperature in Marai Parai. The expected findings could be applied as a reference in the future to increase the potential and management strategies for this carnivorous plant and to allow more research into how climate change affects the number of Nepenthes species and their spatial distribution patterns.